Implementation factors of inculcation of noble values in classroom teaching: case study in Peninsular Malaysia primary schools - Othman, Mohamad Khairi; Mohd Yusoff, Mohd Zailani; Suhid, Asmawati; Puteh, Alis (Elementary Education Online, 2020)
At present, the application of noble values in teaching faces many challenges in its implementation. Therefore, the purpose of this research is to identify the factors that encourage teachers to implement inculcation of noble values in their classroom teaching in primary schools. This study was conducted at four types of schools at North Zone Peninsular Malaysia. This study was used a qualitative approach in the form of case studies. The qualitative approach aims at gaining meaning and a deep understanding of the phenomenon studied from the perspectives of the study participants and not intended to make generalization. The sample in this study consists of eight teachers who teach in four types of schools that have been chosen purposively. The method of data collection is through semi-structured interviews used in this study. The comparative method is continuously used in this study to analyze the primary data collected. The findings show that there are several factors that motivate teachers to implement inculcation of noble values in their teaching such as responsibilities, teachers’ desire, religious factors, class control, subjects’ needs, school environment and culture. The findings of this study are expected to be a guide to improve the quality of implementation of inculcation noble values in classroom teaching.